Optimizing Home Yards with Nutrition Gardens to Support Family Vegetable and Fruit Intake - Aisyah, Iseu Siti; Neni, Neni; Wardani, Yusrima Syamsina; Faturahman, Yuldan; Romdhani, Andhy; Wahyuningtyas, Aulia Putri (Jurnal Abmas Negeri (JAGRI), 2025)
The low consumption of vegetables and fruits in Indonesia remains a nutritional problem that contributes to an increased risk of non-communicable diseases such as hypertension, diabetes, and obesity. One of the efforts to address this issue is through the utilization of home yards as a source of family food. This community service program aimed to improve knowledge, skills, and nutritional awareness by optimizing home yards into nutrition gardens, thereby strengthening household food security, reducing family expenses, and supporting economic improvement. The program was conducted on July 31, 2025 in Sukahurip Subdistrict, Tamansari District, Tasikmalaya City, West Java, with the target participants being “Kelompok Wanita Tani” (KWT) and Posyandu cadres, with a total of 35 participants. The program was conducted using a participatory approach through five stages: socialization, training in gardening skills and nutrition education, application of nutrition garden technology, mentoring, and evaluation. The results showed an increase in participants’ knowledge regarding the benefits of vegetable and fruit consumption as well as the utilization of limited land. The average knowledge score increased from 6,65 (pre-test) to 8,60 (post-test) with p-value = 0,001, indicating a significant difference before and after the intervention. The final evaluation of the program will be carried out through surveis and interviews to assess the improvement in vegetable and fruit consumption, the utilization of home yards as nutrition gardens, and participants’ understanding of balanced nutrition practices.